The efficacy of ultrasound-guided pulsed radiofrequency in the treatment of primary glossopharyngeal neuralgia - Li, Fubo; Lu, Hongcheng; Gong, Gege; Ou, Cehua; Zhang, Yue (Frontiers in Neurology, 2024)
ObjectiveThis study evaluates the clinical efficacy and safety of ultrasound-guided long duration, high voltage pulse radiofrequency (PRF) in managing primary glossopharyngeal neuralgia (GPN).MethodsClinical data were retrospectively analyzed for 13 patients with primary GPN who underwent this treatment between August 2019 and October 2022. Visual Analog Scale (VAS) scores were assessed pre-treatment and at 1 week, 1 month, 3 months, and 6 months post-treatment. Additionally, the rates of discontinuation of oral oxcarbazepine and pregabalin, efficacy, and complication rates at 6 months post-procedure were monitored.ResultsSignificant post-treatment pain relief, was observed across all patients, with statistically significant improvements in VAS scores (p < 0.05). Discontinuation rates for oxcarbazepine and pregabalin were also high (p < 0.05). At the 6-month follow-up, 69.23% of patients achieved excellent and good efficacy, 84.61% demonstrated overall effectiveness, while 15.38% showed poor efficacy. No critical complications were reported in any case.ConclusionUltrasound-guided, long-term, high-voltage PRF effectively relieves primary glossopharyngeal neuralgia and improves quality of life. Featuring ease of operation, high safety and minimal complications making it a promising approach for clinical application.